2023
DOI: 10.3390/app13148198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superhydrophobic Nano-SiO2 on the Hydraulic Conductivity of Expansive Soil and Analysis of Its Mechanism

Abstract: The present work determined the influence of superhydrophobic nano-SiO2 on the hydraulic conductivity and pore size distribution of expansive soil, and analysed the mechanism of modification between superhydrophobic nano-SiO2 and expansive soil from a microscopic view. Superhydrophobic nano-SiO2 was added to expansive soil as a modifier. Our samples were of two types, i.e., unmodified (without nano-SiO2) and modified (with 0.2%, 0.4%, 0.6%, 0.8%, and 1.0% nano-SiO2 by weight of the parent soil). The hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The use of nanotechnology, namely the integration of nano silica particles, in combination with waste products like ash, is one viable route in this respect. Nano silica, with its special properties, may be useful in modifying the mechanical and hydraulic properties of expansive soils [11,12], whereas waste products like ash, which are widely available from various industrial processes, offer a chance to lessen environmental waste and improve soil.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanotechnology, namely the integration of nano silica particles, in combination with waste products like ash, is one viable route in this respect. Nano silica, with its special properties, may be useful in modifying the mechanical and hydraulic properties of expansive soils [11,12], whereas waste products like ash, which are widely available from various industrial processes, offer a chance to lessen environmental waste and improve soil.…”
Section: Introductionmentioning
confidence: 99%
“…As for the insufficient information about nZVI treatment in soil, it becomes evident that the impact of nanomaterials on the deformation and permeability of contaminated soil can vary significantly, referencing other cases of nanomaterial treatment. For instance, the addition of nano-magnesium dioxide to Pb(II) and Zn(II) co-contaminated soil leads to a reduction in the soil's compression index and hydraulic conductivity [34,35]. Furthermore, some studies have indicated that the presence of nano-clay alters the cation exchange capacity (CEC) and specific surface area (SSA) within the system, subsequently increasing permeability and settling in soils with high copper concentrations, up to 30 cmol/kg nitric acid [36].…”
Section: Introductionmentioning
confidence: 99%